What students want a project by Teach for Malaysia - Shashivarmaan Thevaraj; Mohammad Shahril Hashim; Amanda Dina; Aniq Hazis; Muhd. Ikhlas Zidan; Nurida Malik; Saradha Lakshmi (Gerakbudaya Enterprise Teach For Malaysia, 2018)
What Students Want is a student-led book that collects the hopes and dreams of students around Malaysia about what they want for their own learning, the education system, and the future of Malaysia. So much has been said, written and debated about the education in our country, but we often neglect hearing from the students themselves. From stories about what makes a great teacher to standardised testing in schools, students speak up as they reimagine and reflect on their education. The young editorial team hopes you will be inspired and empowered to take steps, no matter how small, towards a revolutionised education system that values what students want for themselves, their communities, and a better Malaysia.